68Ga-PSMA Cerenkov luminescence imaging in primary prostate cancer: first-in-man series. - olde Heuvel, Judith; de Wit-van der Veen, Berlinda J.; van der Poel, Henk G.; Bekers, Elise M.; Grootendorst, Maarten R.; Vyas, Kunal N.; Slump, Cornelis H.; Stokkel, Marcel P. M. (European Journal of Nuclear Medicine & Molecular Imaging, 2020)
Purpose: Currently, approximately 11–38% of prostate cancer (PCa) patients undergoing radical prostatectomy have a positive surgical margin (PSM) on histopathology. Cerenkov luminescence imaging (CLI) using 68Ga-prostate-specific membrane antigen (68Ga-PSMA) is a novel technique for intraoperative margin assessment. The aim of this first-in-man study was to investigate the feasibility of intraoperative 68Ga-PSMA CLI. In this study, feasibility was defined as the ability to distinguish between a positive and negative surgical margin, imaging within 45 min and low radiation exposure to staff. Methods: Six patients were included in this ongoing study. Following perioperative i.v. injection of ~ 100 MBq 68Ga-PSMA, the prostate was excised and immediately imaged ex vivo. Different acquisition protocols were tested, and hotspots on CLI images from the intact prostate were marked for comparison with histopathology. Results: By using an acquisition protocol with 150 s exposure time, 8 × 8 binning and a 550 nm shortpass filter, PSMs and negative surgical margins (NSMs) were visually correctly identified on CLI in 3 of the 5 patients. Two patients had a hotspot on CLI from cancer < 0.1 mm from the excision margin. Conclusion: Overall, the study showed that 68Ga-PSMA CLI is a feasible and low-risk technique for intraoperative margin assessment in PCa. The remaining patients in this ongoing study will be used to assess the diagnostic accuracy of the technique. Trial registration: NL8256 registered at www.trialregister.nl on 04/11/20109.